Korelasi Motilitas Progresif dan Keutuhan Membran Sperma dalam Semen Beku Sapi Ongole Terhadap Keberhasilan Inseminasi - Jalius, Jalius; Depison, Depison (Fakultas Peternakan Universitas Jambi, 2008)
The correlation between the progressive motility and sperm membrane totality in frozen semen of Ongole with artificial insemination success. This experiment was aimed to evaluated the characteristics of progressive motility and spermatozoa membrane totality of Ongole cattle in frozen semen and their correlation to the successful of artificial insemination. The parameters were progressive motility and membrane totality (MT) successful of artificial insemination was measured by non return rate (NR) and conception rate (CR). Result of this experiment showed that PM = 38.14%, MT = 69.86%, NR = 64.49% and CR = 53.47%. Progressive mortality significantly influenced (P<0.05) NR. Mortality and membrane totality significantly determine (P<0.05) the successful of artificial insemination (CR) of Ongole cattle